Histopathological Spectrum of Salivary Gland Tumors and Tumor-like Conditions: A Retrospective Study at a Tertiary Care Centre (GAIMS Journal of Medical Sciences, 2026)
Background: Salivary gland lesions represent a broad and heterogeneous spectrum of both neoplastic and non-neoplastic pathologies. These conditions frequently exhibit significant overlapping histo-morphological patterns, which present considerable diagnostic challenges for pathologists. Definitive characterization of these lesions relies primarily on comprehensive histopathological examination, judiciously supplemented by immunohistochemistry (IHC) to achieve accurate subtyping and to facilitate precise prognostic stratification.Aims and Objectives: This study was meticulously designed with two primary objectives: first, to systematically delineate the histopathological spectrum of salivary gland tumors and tumor-like conditions that are routinely encountered at a major tertiary care referral center. Second, a crucial aim was to critically evaluate the diagnostic yield of fine-needle aspiration cytology (FNAC) and to assess the role of IHC in establishing definitive and accurate diagnoses for these complex lesions.Materials and Methods: A total of fifty-one salivary gland specimens were meticulously subjected to retrospective review. Comprehensive data retrieved from departmental archives. Final diagnoses were stratified into three distinct categories: benign tumors, malignant tumors, and tumor-like or non-neoplastic conditions. FNAC reports were subsequently compared with the histopathological outcomes to compute key diagnostic performance metrics, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy.Results: The study cohort comprised 51 patients, consisting of 29 males and 22 females, which yielded a male-to-female ratio of 1.3:1. The mean age of the cohort was determined to be 43.2. The parotid gland was the most commonly involved anatomical site (80.4%), followed by submandibular gland (11.8%) and minor salivary glands (2%). Benign tumors constituted 45.1% of all cases, while malignant tumors accounted for 19.6%, and tumor-like lesions represented 35.3%. Pleomorphic adenoma (35.3%) emerged as the most frequent benign tumor, with Warthin tumor (7.8%) being the second most common. Mucoepidermoid carcinoma (5.9%) was the most common malignancy. Tumor-like conditions, primarily constituted chronic sialadenitis (17.6%). FNAC demonstrated 86.7% diagnostic accuracy, with 100% specificity but only 33.3% sensitivity for malignancy (n=30). Selective IHC, including markers like DOG-1 and SOX10, provided crucial diagnostic information, and the Ki-67 index ranged from 3-10%.Conclusion: Benign tumors, particularly pleomorphic adenoma, unequivocally predominated within this series, with mucoepidermoid carcinoma identified as the most frequently encountered malignancy. FNAC consistently demonstrated excellent specificity but exhibited notable limitations in sensitivity for malignancy detection. Consequently, the judicious and problem-oriented application of IHC substantially enhanced diagnostic accuracy in cases presenting with morphologically ambiguous lesions, highlighting its indispensable role in definitive diagnosis.